WiMAX Implementation as Existing Hotspot Network Backhaul in Jakarta - Sirat, Djamhari; Asvial, Muhamad; Marpaung, Luther B. (UI Scholars Hub, 2010)
WiMAX Implementation as Existing Hotspot Network Backhaul in Jakarta The development of Broadband Wireless Access (BWA), such as WiMAX, as a global standard for data transmission media has been used by high speed internet access provider. WiMAX application which supported by capabilities of interoperability, flexibility and commercial aspect make the internet services become more efficient, cheaper and easier to the customer. This phenomenon should be responded by ISPs. Based on technical and financial aspect in deciding the implementation of Wireless Network with WiMAX technology as a substitute, this research will observe and analyze the projection of WiMAX technology implementation as a backhaul for the existing Wi-Fi’s network in Jakarta. This paper will describe the calculation based on the amount of hotspots registered in IIX and average peak traffic per regional from technical aspect with several pricing and technology combination. The result give the basic figures in investing WiMAX as substitute technology for backhaul in hotspot network and also will show its growth in 5 years.